Exploring health and wellbeing in prison: a peer research approach. Issue 1 (24th September 2019) - Perrett, Stephanie E.; Gray, Benjamin J.; G., L.; E., D.; Brooks, Neville J.
Abstract : Purpose: Those in prison have expert knowledge of issues affecting their health and wellbeing. The purpose of this paper is to report on work undertaken with male prisoners. This paper presents learning and findings from the process of engaging imprisoned men as peer researchers. Design/methodology/approach: The peer researcher approach offers an emic perspective to understand the experience of being in prison. The authors established the peer research role as an educational initiative at a long-stay prison in Wales, UK to determine the feasibility of engaging imprisoned men as peer researchers. Focus groups, interviews and questionnaires were used by the peer researchers to identify the health and wellbeing concerns of men in prison. Findings: The project positively demonstrated the feasibility of engaging imprisoned men as peer researchers. Four recurring themes affecting health and wellbeing for men in a prison vulnerable persons unit were identified: communication, safety, respect and emotional needs. Themes were inextricably linked demonstrating the complex relationships between prison and health. Originality/value: This was the first prison peer-research project to take place in Wales, UK. It demonstrates the value men in prison can play in developing the evidence base around health and wellbeing in prison, contributing to changes within the prison to improve health and wellbeing for all.